Water Quality Monitoring and Control System in Koi Fish Cultivation Based on Internet-of-Things (IoT) - Ahmad, Ali Hanafi; M.Yanis, Naili Ikrimah; Nur Irawan, Muhammad Naufal; Munadi, Rendy; Fitriyanti, Nurwulan (Jurnal Rekayasa Elektrika, 2025)
This research develops an Internet-of-Things (IoT)-based system for real-time monitoring and automatic control of water quality in koi fish farming, addressing the lack of knowledge regarding optimal water conditions. The system integrates sensors for pH, ammonia, temperature, total dissolved solids (TDS), and turbidity, along with controllers such as filters, coolers, and heaters, all managed through a mobile application called AquaKoi. System testing is divided into IoT device testing and mobile application testing. IoT device testing ensures proper sensor and controller functionality, with sensor data verified against water quality standards. Application testing includes black box testing, quality-of-service (QoS) measurement, user acceptance test (UAT), and notification warning testing, showing a user satisfaction rate of 92%. The test results indicate that the system functions well and meets specifications, despite challenges like overheating of the ESP32 microcontroller, which was mitigated with a temporary fan solution. Overall, the AquaKoi system demonstrates significant potential in enhancing the efficiency of koi fish farming. However, further development is recommended to address technical constraints, improve the user interface, and expand the systems capabilities to meet more diverse user needs.